Eguana reports – servidor de reportes basado en tecnología java y xml - Cox Sosa, Roy Stalin (2010)
Eguana Reports is a reporting system developed by students of the Graduate Topic "Transactional Application Development with Java and XML". The system shows the extensive use of technology Java EE (Java Enterprise Edition). Under this platform can be found, within the project, several open source tools integrated in order to achieve a goal. This paper also can be a practical guide for those developers interested in Java EE. Eguana Reports, as a module, is the solution to the need for reporting of E-Guana. E-Guana is an initiative for an E-Procurement system implementation, developed in modules by the other students on the topic of graduation. Despite this, the reporting system does not depend on other modules to function. Eguana Reports is a standalone application. It can integrate with any application using a data source and generate custom reports from these.